Unveiling unmasked faces: a novel model for improved mask detection using haar cascade technique - Kumar, Sanjeev; Kumar, Mohit; Dubey, Kriti; Sharma, Kaushal (SHM Publisher, 2023)
In response to the urgent need to enforce mask-wearing compliance during the COVID-19 pandemic, this